Influência da luminosidade na morfometria foliar e estrutura arbórea de Pilocarpus pennatifolius Lem. - Silva, Janderson de Oliveira (2019)
Tropical forests with their plant diversity have a vertical structure stratified by the light demand of the different species. At lower levels occur many species with potential to provide non-wood products, especially leaves. The sustained uses of these forest resources presuppose the knowledge of the requirements of a given species for light or its morphological and foliar plasticity shaped by the density of trees and the quality of the site. Aiming at the management to produce leaves three 100 m² samples were evaluated in small pure populations of Pilocarpus pennatifolius Lem. (Jaborandi) occurring in the canopy understory dominated by hardwoods in natural forest formation in Serra Geral in Rio Grande do Sul in the municipality of Pinhal Grande. The trees were observed for leaf morphometry and weights in different density conditions, tree height class, luminosity and litter accumulation, and soil organic matter. In the denser samples the luminosity is significantly lower and the accumulation of litter and organic matter in the soil are higher. The leaf morphometric variables resulted in positive and significant correlations for leaf area, green weight and dry weight, as well as differences between averages of leaf thickness between the samples. Leaf morphometry differed significantly in the comparison between the samples in the class of the highest trees. The dry weight, variable of greater interest, presented small differences between tree height classes as between samples, presenting, significantly, lower weight only in the highest of the sample with greater luminosity, indicating that the production can be obtained from populations of sub -wood in varied densities.